Mentoring Program in Talent Development at Sekolah Bisnis Muda (SBM) Bogor and Sekolah Muda Mandiri (SMM) Semarang - Budi, Setyo; Ahmad; Rahman, Imas Kania (TAWAZUN: Jurnal Pendidikan Islam, 2024)
It is undeniable that cases of bullying and pornography in teenagers are increasingly common as information technology develops. The two cases above are quite worrying for parents and teachers and even more dangerous for the future of the children themselves. On the other hand, adolescence is a subculture in adult life. At this time, potential begins to appear, both physical potential and potential nature. Good assistance in this phase will have a positive impact on the development of the next phase. The purpose of this study is to analyze the extent to which the mentoring program that has been implemented accommodates the need for adolescent talent development. This research uses a qualitative field method used to describe the Islamic mentoring program as a result of information obtained directly from informants, observations, and document studies. The mentoring program at SBM Bogor is a method of teaching and learning activities based on Islamic guidance. So that all learning activities that are followed such as finance, business mentality, business mindset, English, Islamika, literacy, Arabic, and video graphics use Islamic mentoring methods. The mentoring program targets the growth of students in developing their business talents. The mentoring program at SMM Semarang is able to deliver students to understand Islamic material easily. However, the mentoring program is not enough to facilitate students' talent development. Nevertheless, it has answered the need for students' worship, adab, ethics, and moral problems. Abstrak Tidak bisa dipungkiri bahwa kasus perundungan dan pornografi pada remaja semakin sering di dengar seiring berkembangnya teknologi informasi. Dua kasus tersebut cukup mengkhawatirkan orang tua dan guru dan lebih lagi adalah bahaya bagi masa depan anak itu sendiri. Di sisi lain, remaja adalah subkultural dalam kehidupan manusia dewasa. Pada masa ini, potensi mulai terlihat, baik potensi fisik maupun potensi sifat. Pendampingan yang baik pada fase ini akan berdampak positif pada perkembangan fase selanjutnya. Tujuan penelitian ini untuk menganalisis sejauh mana program mentoring yang telah dilaksanakan mengakomodasi kebutuhan akan pengembangan bakat remaja. Penelitian ini menggunakan metode kualitatif lapangan yang digunakan untuk mendeskripsikan program mentoring islami hasil informasi yang diperoleh langsung dari narasumber (informan), hasil pengamatan (observasi), dan studi dokumen. Program mentoring di SBM Bogor merupakan metode kegiatan belajar mengajar berdasar tuntunan Islam. Sehingga semua kegiatan belajar yang diikuti seperti keuangan, mental bisnis, mindset bisnis, english, islamika, literasi, bahasa arab, dan video grafi itu menggunakan metode mentoring islami. Program mentoring menargetkan tumbuhnya siswa dalam mengembangkan bakat bisnisnya. Program mentoring di SMM Semarang mampu mengantarkan siswa memahami materi keislaman dengan mudah. Namun program mentoring belum cukup memfasilitasi pengembangan bakat siswa. Meskipun demikian, sudah menjawab kebutuhan akan permasalahan ibadah, adab, etika, dan moral siswa.